LEGAL ANALYSIS OF LEGAL PROTECTION FOR VICTIMS OF THE CRIMINAL ACTS OF EMBAGARY OF TWO-WHEEL VEHICLES (STUDY OF DECISION NUMBER 858/PID.B/2025/PN.LBP) - Belovit Eva Lubis; Hisar Siregar; Samuel Situmorang (RADJA PUBLIKA, 2026)
This study examines legal protection for victims of motorcycle imbezzlement and a critical analysis of the judge's considerations in Decision Number 858/Pid.B/2025/PN.LBP using a normative juridical method with statutory, case, and conceptual approaches. Defendant Muklis Pranoto was proven to have embezzled the victim's motorcycle by pawning it for Rp. 500,000 from a value of Rp. 7,000,000 for online gambling, and was sentenced to 2 years in prison under Article 372 of the old Criminal Code (Article 486 of the National Criminal Code). The judge's selection of Article 372 was dogmatically correct, as criminal intent arose only after legal possession of the vehicle, rendering Article 378 inapplicable. However, serious gaps in victim protection were identified: the prosecutor did not seek restitution, the seeking mechanism (Articles 98–101 of the Criminal Procedure Code) was not pursued, and the judge did not order residual restitution of Rp. 6,500,000. Restorative justice evaluation reveals the verdict only partially fulfills restorative elements, lacking formal dialogue, full restitution, and LPSK involvement. Systemic reform in the implementation of Law No. 31 of 2014 and Supreme Court Regulation No. 1 of 2022 is urgently needed.